Integrative profiling of extrachromosomal circular DNA in placenta and maternal plasma provides insights into the biology of fetal growth restriction and reveals potential biomarkers - Lin, Minhuan; Chen, Yiqing; Xia, Shuting; He, Zhiming; Yu, Xuegao; Huang, Linhuan; Lin, Shaobin; Liang, Binrun; Huang, Ziliang; Mei, Shiqiang; Liu, Dong; Zheng, Lingling; et al. (Frontiers in Genetics, 2023)
Introduction Fetal growth restriction (FGR) is a placenta-mediated pregnancy complication that predisposes fetuses to perinatal complications. Maternal plasma cell-free DNA harbors DNA originating from placental trophoblasts, which is promising for the prenatal diagnosis and prediction of pregnancy complications. Extrachromosomal circular DNA (eccDNA) is emerging as an ideal biomarker and target for several diseases. Methods We utilized eccDNA sequencing and bioinformatic pipeline to investigate the characteristics and associations of eccDNA in placenta and maternal plasma, the role of placental eccDNA in the pathogenesis of FGR, and potential plasma eccDNA biomarkers. Results Using our bioinformatics pipelines, we identified multi-chromosomal-fragment and single-fragment eccDNA in placenta, but almost exclusively single-fragment eccDNA in maternal plasma. Relative to that in plasma, eccDNA in placenta was larger and substantially more abundant in exons, untranslated regions, promoters, repetitive elements [short interspersed nuclear elements (SINEs)/Alu, SINEs/mammalian-wide interspersed repeats, long terminal repeats/endogenous retrovirus-like elements, and single recognition particle RNA], and transcription factor binding motifs. Placental multi-chromosomal-fragment eccDNA was enriched in confident enhancer regions predicted to pertain to genes in apoptosis, energy, cell growth, and autophagy pathways. Placental eccDNA–associated genes whose abundance differed between the FGR and control groups were associated with immunity-related gene ontology (GO) terms. The combined analysis of plasma and placental eccDNA–associated genes in the FGR and control groups led to the identification of potential biomarkers that were assigned to the GO terms of the epigenetic regulation of gene expression and nutrient-related processes, respectively. Conclusion Together, our results highlight links between placenta functions and multi-chromosomal-fragment and single-fragment eccDNA. The integrative analysis of placental and plasma eccDNA confirmed the potential of these molecules as disease-specific biomarkers for pregnancy complications.